Mukah District Office / Sharonessa Umang Layang - Layang, Sharonessa Umang (University Technology MARA Sarawak, 2019)
The district of Mukah is the heart of the Mukah Division which is the administrative centre of the district. The Mukah District Office is located on the lower level of the Royal Pehin Tower. The area is 1,366.00 km2 and it covers the Balingian Sub-District with 1,170.00 km2. The area is largely covered by swamps. Mukah district can be reached in three ways: by land, water and air. The distance between Mukah and Sibu is 180 km. Besides, Mukah is the largest district within the district. The Mukah District Administration began as early as 1911 under the administration of a District Officer named Henry Herbert Kortright. The Mukah District Administration at that time was under the jurisdiction of the Third Division. The Administrative Center of the British Colonial Government in Mukah District was at the Fort Burdett II Building, built around 1910- 1911. When the Second World War erupted between 1939 and 1945, the Fort Burdett II Building was destroyed (Official Website of Administrative Division of Mukah Division, 2019).